Influence of process conditions on the physicochemical properties of jussara pulp (Euterpe edulis) powder produced by spray drying - Santana, Audirene Amorim [UNESP]; Paixão, Louryval Coelho; De Oliveira, Rafael Augustus; Telis, Vânia Regina Nicoletti [UNESP] (FapUNIFESP (SciELO), 2018)
The objective of this work was to optimize the spray drying of jussara pulp using mixtures of modified starch (MS) with whey protein concentrate (WPC) or soy protein isolate (SPI) as the carrier agents. Two central composite rotatable designs were used to evaluate the effect of the independent variables of inlet air temperature (140 °C to 200 °C), carrier agent concentration - CAC (0.5 to 2 g carrier agent/g jussara pulp solids) and the proportions of MS:WPC or MS:SPI (5 to 30 g WPC or SPI/100 g carrier agent) on the following responses for powders formulated with MS:WPC and MS:SPI, respectively: moisture content (0.3% to 1.4% and 0.6% to 1.2%), solubility (78.0% to 92.9% and 78.9% to 83.8%), retention of total anthocyanins (49.2% to 82.9% and 34.1% to 96.9%), encapsulation efficiency (98.5% to 99.7% and 98.5% to 99.5%), hue angle (9.1 to 44.0 and 3.7 to 42.6), chroma (10.0 to 15.3 and 9.2 to 14.3) and process yield (33.2% to 55.5% and 49.9% to 78.5%). The inlet air temperature 170 °C, CAC of 1.25 and 2 g/g jussara pulp solids and proportion of MS:WPC or MS:SPI of 17.5 and 30 g/100 g were recommended as the selected conditions.
Keywords: Euterpe edulis Martius; Modified starch; Response surface methodology; Soy protein isolate; Whey protein concentrate